Post-Traumatic Stress Disorder among Burn Patients in a Tertiary Hospital - Hasan, Md Iqbal; Rahman, Md Shafiqur; Shaheen, Rukhsana (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Imbalance in multi-factorial components of human ecology plays a role in developing post-traumatic stress disorder hampering economical productivity and normal social life. Objectives: To find out the interplay of issues that are conducive to the outcome of the disorder among hospital admitted burn patients. Materials and Methods: This unobtrusive qualitative behavioral health research by in-depth interview was conducted among conveniently selected 35 burn patients in Dhaka Medical College Hospital of Bangladesh from July 2013 to June 2014. The data were analyzed to draw conclusion through etic and/or emic interpretation. All ethical issues were taken care of. Results: The highest 80% burn patients were married, 71% were male, and 80% were Muslim. Majority 37.14% were day laborer, 28.57% had completed primary education, 34.29% belonged to the age group 21-30 years, and 43% had monthly family income up to Tk. 10000. Of 41% burn occurring at home, majority 27% occurred during rice cooking, affecting the upper limb in 29% cases. Social dislocation was the major phenomena leading to burn injury in 22.86% of the patients. Lack of harmonious relationship and in-laws poking in conjugal life sometime led to deliberate infliction of burn. Conclusion: The study concluded with the suggestions for prevention of neoteric entry in the domain of post-traumatic stress disorder through social movement and psychotherapy of burn patients. Study also hinted for further probing of the phenomenon of the disorder. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 27-31